Conjecture sur le comportement de l’impôt sur le revenu des particuliers - Boucher, Michel; Lebel, Jean-Guy (L'Actualité économique, 1973)
AbstractThis fiscal essay tries to specify the economic variables which have an effect upon the personal income tax during a business cycle.After clearing out the concept of trend elasticity and cyclical elasticity, we propose a model based on the concept of elasticity which will permit us to see the income increases due to the overall increase in employment (or a decrease in the rate of unemployment), and those produced by the global increase in wealth (such as the increase in per capita revenue due to productivity, inflation and so on).Then we apply this model to the federal personal income tax collected in Quebec for ten income classes and we find that there is a difference between the average taxation rate due to the increment of employment and the average taxation rate due to wealth increase and consequently at the elasticity level also. However, the difference is not statistically significant.So, our theoretical model and its application explains partly why the income elasticity of the personal income tax appears to be greater in periods of decline in economic activity and tends to abate fairly sharply as expansionary momentum is restored.